ANALISIS DAN PENYUSUNAN MODEL BUKU TEKS BAHASA INDONESIA SMK BERBASIS PENDIDIKAN KECAKAPAN HIDUP. - Kosasih, - (2010)
This research is motivated by the importance of books in the teaching-learning process. Based on this backgroundthen author formulated six issues for this research, namely as follows: (1) how is the structure of language skills material in the vocational high school curriculum forBahasaIndonesia Lesson in relation to the development of life skills of the students? (2) howis the existence of life skillsmaterials in the textbooks of vocational high school for Bahasa Indonesia Lesson? (3) howare vocational high school teachers respond to Bahasa IndonesiaLesson textbook in relevance to the purposes of the students in developing life skills? (4) howare the perceptions of vocational high school students to the textbooks they use? (5) howis the relevance of Bahasa IndonesiaLesson textbooks based vocational aspects of life skills education? (6) howis the model ofBahasaIndonesia Lesson textbook which is ideal forthe development of life skills forvocational high school students?To answer thatsixproblems, author conducted literature study to get several theories and opinions regarding to the concepts of compilation of textbooks in the relevance to the development of life skills education. Then,author combined these theories with empirical data in the field which is gained through research techniques of content analysis, interviews, and questionnaires.Based on the above, authorgot a number of findings as follows. In the vocational high school curriculum of Bahasa Indonesia Lesson, there is a different emphasis on life skills education, especially for aspects of self-awareness, academic skills, and vocational. In general, BahasaIndonesia Lesson textbooks of the vocational high school had not yet developed a life skills education optimally. This is particularly true for aspects of self-awareness, vocational skills and academic skills. Meanwhile, the teachers argued that they are easy on developing of the curriculum in conjunction with importance of life skills education. The concept of life skills education is not new at all because for them as a vocational high school teachers has been required to direct the lesson materials to the practical things. Opinion of the students of the textbooks they use is that the textbook was quite helpful to understand their strengths or weaknesses in the language skill. Therefore, the concept of life skills education needs to be developed optimally. The exercises contained in the textbooks had not matched yet withthe purposes of the studentsas skilled labor candidates. Activities in the textbook also do not support students' learning experiences. For that, author formulated all textbook compilation model in accordance with the needs of the students with life skills-based education.